The effects of epoxyacrylate coating on printability of bio/synthetic-based fabrics in a thermal transfer printing system - (:unkn) unknown (Bulgarian Academy of Sciences, 2019)
This study was aimed to determine the effect of epoxyacrylate oligomer on the print quality. For this purpose, the test print image, transferred on polyester film using a digital printing system, was applied on three different textile fabrics using thermal transfer printing system at three different temperatures. Then, epoxyacrylate based coating formulation was applied on the printed textile fabrics. In order to determine the printability parameters, print colors L*, a*, b* and gloss values were measured on uncoated and epoxyacrylate coated printed textile fabrics. Then a standard washing process was applied on uncoated and epoxyacrylate coated printed textile fabrics in order to estimate the washing fastness of the coating and printing processes. Results showed that print chroma values of epoxyacrylate coated fabrics decreased whilst print gloss values increased. But, after the washing step, print gloss values of uncoated and epoxyacrylate coated printed textile fabrics all remained unchanged. Furthermore, epoxyacrylate coating has no significant effect on print lightness values of printed textile fabrics. The change in textile fabrics’ structures did not show a distinct effect on printability parameters. © 2019 Bulgarian Academy of Sciences, Union of Chemists in Bulgaria
Keywords: Epoxyacrylate coating; Print gloss; Thermal transfer printing